(untitled) (Modern Problems of Metallurgy, 2020)
suggested for making the side frames of freight cars bogies by casting two parts models – the main 20GL and alternative 20G1FL, 30GSL grade steels, which differ in content of alloying components, which have due to this different kinetics of structural formation and, as a consequence, the final structure, which allows for forecasting capabilities varying classes of products strength – K25, K30 and K35, correspondently.